Hearth as a Source for Population Studies of the Kyiv Voivodeship in the Middle of the Eighteenth Century - Dmytro Kolomiiets (Київські історичні студії)
This article is focused on the sources of fiscal records of the Polish-Lithuanian Commonwealth, namely the Hearth Tax Register of 1754. The purpose of this study is to calculate the population of the Kyiv Voivodeship based on the information of the Hearth Tax Register. The research methodology is based on the principles of historicism, scientificity, objectivity and systematicity. Special attention is paid to the study of data from the source, for which statistical analysis and comparison methods are used. The information from fiscal sources, podymny registers in particular, is necessary for calculating the population of a region or its individual settlements. Using information from fiscal records allows for a broader understanding of the population issues, and in combination with sources of economic or statistical use, it provides the opportunity to explore not only quantitative indicators but also individual demographic characteristics. Pastoral lists or starosta inventories would help to confirm or refute the information in the Hearth Tax Register, as well as supplement it with comparative analysis (provided that the entire range of sources covers a particular period of time). The calculation of the population by powiats or smaller territorial units makes it possible to track the development of individual parts of the voivodeship. It is also possible to characterise the urbanization of such entity as Kyiv Voivodeship using the information obtained. The available information makes it possible to get a glimpse of the evolution or degradation of settlements over time, and the merger of settlements into larger formations.